Levels of Physical Activity and Prevalence of Musculoskeletal Disorders Among Physicians in Saudi Arabia Post COVID-19 Lockdown: An Epidemiological Cross-Sectional Analysis - Reem S. AlOmar (SAGE Publishing, 2021)
Introduction: Musculoskeletal disorders (MSDs) are common worldwide. Recommendations to reduce discomfort often commence with increasing physical activity levels. In Saudi Arabia, levels of physical activity prior to the COVID-19 pandemic were low. This cross-sectional study aims at estimating the prevalence of MSDs among Saudi physicians, as well as determining the pattern and level of physical activity post lockdown and examining their association. Methods: Physical activity levels were assessed via the International Physical Activity Questionnaire and MSDs were assessed via the Nordic Musculoskeletal Questionnaire. Chi-squared tests with significance levels of <.05 were performed to explore bivariate associations. Unadjusted and adjusted odds ratios (ORs) along with their 95% confidence intervals (CIs) were given by binary logistic regression analyses. Results: A total of 3492 physicians participated in this study, and over half of them (63.55%) reported low physical activity. Risk of MSDs increased with aging and with increasing BMI ( P for trend <.05). Females were more likely to report MSDs (OR = 1.23, 95% CI = 1.07-1.86), as well as physicians with a chronic condition (OR = 1.52, 95% CI = 1.24-1.37) and those who work in shifts (OR = 1.18, 95% CI = 1.03-1.37). Moderate activity conferred a non-significant protective effect (OR = 0.95, 95% CI = 0.79-1.13), whilst high physical activity had a non-significant increased risk of MSDs in this population. Conclusion: Physical activity in this population is astonishingly low, while prevalence of MSDs is relatively high. Significant factors include age, sex, shift work, and the presence of chronic conditions. Current results warrant the consideration of preventive measures for physicians.